1998
DOI: 10.1002/(sici)1097-4628(19980222)67:8<1393::aid-app5>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of tussah silk fibers graft-copolymerized with methacrylamide and 2-hydroxyethyl methacrylate

Abstract: Tussah silk fibers were graft-copolymerized with methacrylamide (MAA) and 2-hydroxyethyl methacrylate (HEMA) in aqueous media, using a chemical redox system as an initiator. High weight gain values were obtained with both grafting agents (up to 175%). The extent of homopolymerization was negligible for the MAA grafting system over the entire range of monomer-silk ratios examined, while polymer deposition on the fiber surface occurred when the HEMA-silk ratio exceeded 0.5% (w/w). The moisture content of poly(MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 5 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Different studies have shown that grafting may cause slight or severe changes in the thermal behavior of the fibers, the extent of which depends on several parameters, such as the kind of used monomer, grafting conditions and grafting percentage [5][6][7]. The results of DSC are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have shown that grafting may cause slight or severe changes in the thermal behavior of the fibers, the extent of which depends on several parameters, such as the kind of used monomer, grafting conditions and grafting percentage [5][6][7]. The results of DSC are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, silk crease recovery, dimensional stability, rub resistance, photo yellowing, oil and water repellency, color fastness, have been dramatically improved [5,6] by means of grafting. In the case of wool, the internal deposition of different polymers may change tensile properties, felting shrinkage, abrasion and pilling resistance, hygroscopicity, chemical resistance, thermal stability, dying behavior, rot resistance, durability and bacterial resistance [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 2405 and 2108 cm −1 represent characteristic α‐helical and β‐sheet conformation of AASF . Besides, the spectral patterns are further characterized by the peaks at 1665 (amide I), 1234 (amide III), and 1083 cm −1 which are assigned to β‐sheet conformation whereas the peaks at 1058, 945, and 906 cm −1 arise from α‐helical conformation of fibroin region containing polypeptide (poly(‐Gly‐Ala) chain) sequences . From Figures a–c, it appears that position and intensity of the peaks characteristics of β‐sheet AASF remain essentially unchanged.…”
Section: Resultsmentioning
confidence: 93%
“…They are also hydrophobic and hygroscopic in nature with unique honeycomb structure which is accountable for their high thermal resistance properties [15]. CFF can be modified by grafting to enhance some of its naturally poor properties such as dimensional stability, rub resistance, oil and water repellency, tensile properties, abrasive and peeling resistance [16][17][18][19]. CFF have been used to reinforce a number of different polymeric materials for diverse applications.…”
Section: Introductionmentioning
confidence: 99%